Gearing macroeconomic policies to manage large inflows of ODA: The implications for HIV/AIDS programmes - Anis Chowdhury; Terry McKinley (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper examines how macroeconomic policies can be managed to accommodate a large inflow of foreign aid to combat the HIV/AIDS epidemic and still maintain macroeconomic stability. Because of the daunting scale of this epidemic, funds need to be disbursed urgently in order to contain its spread, yet some economists worry that rapidly scaling up foreign assistance for this purpose will cause inflation and appreciation of the real exchange rate. If such effects occur, they could impair a country's international competitiveness and endanger its growth prospects. However, this paper maintains that such effects can be minimized if governments and central banks coordinate fiscal, monetary and exchange rate policies. If they do, they should be able to both `spend' aid in order to finance larger government programmes and `absorb' aid in order to import more real resources. Often, governments that receive foreign aid neither spend nor absorb it fully, defeating the basic purpose of development assistance. Because governments fear inflation, they are reluctant to finance a significant increase in spending on HIV/AIDS programmes even when the funding is available. Central banks are reluctant to sell the foreign currency they receive from HIV/AID related aid because they fear that such an action might appreciate the domestic currency. However, if aid-induced spending on HIV/AIDS programmes minimizes the adverse impact of the epidemic on human capabilities, not only would it combat a grave human development crisis but also it could safeguard long-term economic growth. Instead of adhering to restrictive macroeconomic policies, governments could target their increased spending on productivity-enhancing public investment and central banks could amplify the flow of low-cost credit to stimulate private investment. The central banks must accept some appreciation of real exchange rate, as only through appreciation are more imports possible. However, if the real exchange rate does appreciate excessively to the detriment of exports, the central bank can implement means to manage its fluctuations in order to maintain competitiveness. Moreover, if a significant proportion of HIV/AIDS funds is used to directly finance the import of drugs and medical equipment that are not produced domestically (which is often the case), there is likely to be even less impact on inflation or appreciation of the exchange rate.
Keywords: F35; F41; F43; O11; 330; foreign aid; Dutch disease; HIV/AIDS; macroeconomic policies; AIDS; Wirtschaftspolitik; Entwicklungshilfe; Dutch Disease